Proporsi Daging Analog-Tepung Tempe pada Pembuatan Patty: Karakteristik Sensori dan Kesukaan Konsumen - Retno Yuliya Puspita Sari; Any Sutiadiningsih; Mauren Gitta Miranti; Aisyah Nurin Kamilya (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is driven by the high dependence on meat in patty products, making it necessary to use local food ingredients as an alternative. The study aims to find out the sensory characteristics of patties with different proportions of analog meat and tempeh flour, determine consumer preference levels, and identify the best formulation. The research used an experimental method with three treatment proportions of analog meat and tempeh flour, namely 70%:30%, 60%:40%, and 50%:50%. Data were obtained through observations using sensory characteristic sheets and hedonic tests. Sensory characteristic tests were carried out by 12 panelists, while consumer preference tests involved 35 panelists consisting of 5 trained panelists and 30 untrained panelists. The data were analyzed using the Friedman test followed by the Wilcoxon Signed Rank test. The results showed that the proportion of analog meat and tempeh flour resulted in differences in the sensory characteristics. The research results show that the proportion of meat analog and tempeh flour causes differences in sensory characteristics and consumer liking levels. The treatment with 70% meat analog and 30% tempeh flour got the highest liking score and was determined as the best formulation. This formulation produced color, aroma, taste, and texture that were more acceptable to consumers compared to the other treatments. The implication of this research is that using 30% tempeh flour can be utilized as a local food ingredient in developing plant-based patties that have good sensory characteristics and are potentially accepted by the public.